Synthesis and Antiproliferative Activity of Marine Bromotyrosine Purpurealidin I and Its Derivatives - Bhat, Chinmay (Mar Drugs, 2018)
The first total synthesis of the marine bromotyrosine purpurealidin I (1) using trifluoroacetoxy protection group and its dimethylated analog (29) is reported along with 16 simplified bromotyrosine derivatives lacking the tyramine moiety. Their cytotoxicity was evaluated against the human malignant melanoma cell line (A-375) and normal skin fibroblast cells (Hs27) together with 33 purpurealidin-inspired simplified amides, and the structure–activity relationships were investigated. The synthesized simplified analogs without the tyramine part retained the cytotoxic activity. Purpurealidin I (1) showed no selectivity but its simplified pyridin-2-yl derivative (36) had the best improvement in selectivity (Selectivity index 4.1). This shows that the marine bromotyrosines are promising scaffolds for developing cytotoxic agents and the full understanding of the elements of their SAR and improving the selectivity requires further optimization of simplified bromotyrosine derivatives.